If f(y)=y1-y2,g(y)=y1+y2,then (fog)(y) is equal to 

If f(y)=y1-y2,g(y)=y1+y2,then (fog)(y) is equal to 

  1. A

    y1-y2

  2. B

    y1+y2

  3. C

    y

  4. D

    1-y21-y2

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    f(y)=y1-y2,g(y)=y1+y2and fogy=fgy=fy1+y2=y1+y21-y21+y2=y1+y211+y2=y

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.